Design and characterization of axisymmetric auxetic metamaterials. (1st October 2020) - Yang, Hang; Ma, Li
Abstract: Traditional three dimensional (3D) block auxetics exhibit anisotropic cross-section changes even they exist in isotropic forms due to finite size and boundary effect. Herein, a systematic design strategy of axisymmetric auxetic metamaterials is proposed with rotationally symmetric transverse deformation mode. The axisymmetric auxetics are obtained by the revolution of two-dimensional curved auxetic configurations along the axis of rotation and composed with shell elements. Finite element simulations and mechanical experiments reveal that the axisymmetric deformation mechanism cause transversely isotropic negative Poisson's ratio and enhance the specific Young's modulus compared to corresponding 2D and 3D cellular structures. The influence of geometric parameters on elastic constants is investigated numerically. Three kinds of 3D printing technologies are adopted to fabricate the axisymmetric auxetics which shows the relative Young's modulus and equivalent Poisson's ratio are independent of constitute materials. This study systematically characterizes the mechanical responses of axisymmetric auxetic metamaterials and expounds the potential multifunctional applications, such as reusable energy absorption.